2018
DOI: 10.1002/14651858.cd012991
|View full text |Cite
|
Sign up to set email alerts
|

Motor neuroprosthesis for promoting recovery of function after stroke

Abstract: BackgroundMotor neuroprosthesis (MN) involves electrical stimulation of neural structures by miniaturized devices to allow the performance of tasks in the natural environment in which people live (home and community context), as an orthosis. In this way, daily use of these devices could act as an environmental facilitator for increasing the activities and participation of people with stroke. ObjectivesTo assess the e ects of MN for improving independence in activities of daily living (ADL), activities involvin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(17 citation statements)
references
References 58 publications
0
17
0
Order By: Relevance
“…Records excluded (n = 1255) characteristics of the included reviews, grouped by patient population. The majority of the reviews focused on stroke populations (n = 16), 29,[31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] followed by SCI (n = 5), 30,[46][47][48][49] MS (n = 2) 50,51 and one with mixed populations. 52 No reviews of PD, adult CP or TBI were found.…”
Section: Included Reviewsmentioning
confidence: 99%
See 4 more Smart Citations
“…Records excluded (n = 1255) characteristics of the included reviews, grouped by patient population. The majority of the reviews focused on stroke populations (n = 16), 29,[31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] followed by SCI (n = 5), 30,[46][47][48][49] MS (n = 2) 50,51 and one with mixed populations. 52 No reviews of PD, adult CP or TBI were found.…”
Section: Included Reviewsmentioning
confidence: 99%
“…However, for two reviews it was not clear whether the interventions in the included studies investigated FES or NMES as defined in this umbrella review. 35,43 The majority (n = 15) of the reviews included studies reporting on both single and multi-channel stimulation, 29,30,[35][36][37][38][39][40][41][42][43]45,[50][51][52] with two reviews including only studies which investigated the effect of singlechannel stimulation. 32,33 The remaining reviews did not report this information.…”
Section: Included Reviewsmentioning
confidence: 99%
See 3 more Smart Citations